A sticky proposition: The endothelial glycocalyx and von Willebrand factor. (26th February 2020) - Choi, Seon Jae; Lillicrap, David
Abstract: Von Willebrand factor (VWF) is a critical component of the hemostatic system. Basal secretion of VWF from endothelial cells is the principal determinant of an individual's baseline plasma VWF levels, while endothelial VWF release can also be induced by several biochemical agonists and biomechanical forces such as increased shear stress. However, the mechanotransduction machinery responsible for this latter response is unclear. Here we propose that the endothelial glycocalyx (EGC), a dynamic layer of proteins and carbohydrates that covers the surface of the vascular endothelium, may play a key role in mediating this response. The EGC has previously been implicated in mediating the mechanotransduction of shear stress in other shear‐responsive endothelial processes, such as nitric oxide production and stem cell differentiation. Here, we hypothesize that a similar mechanism may be responsible for the basal secretion of endothelial VWF, whereby the EGC mediates the mechanotransduction of physiological shear stress generated by flowing blood, that in turn contributes to the maintenance of physiological plasma VWF levels.